nalysis of a Research Instrument to Map English Teachers’ Proficiency - Siti Mina Tamah; Anita Lie (IJEE (Indonesian Journal of English Education), 2019)
ABSTRACTTeachers’ English proficiency can be measured by designing a research instrument  in a form of test. The devised test must fulfill the requirement of a good test. This article is aimed at discussing item analysis centering on multiple choice questions used to measure the proficiency of Indonesian High School teachers involved in English instruction. The first set of syllabus oriented test is tried out to 20 subjects, and the second set – general English oriented – to 28 subjects. The test analysis indicates the item difficulty indices range from .20 to 1 for the first set and .07 to .89 for the second set. With regard to item discrimination analysis, the study finds the d values range from -0.33 to 1.0 for the first set, and -0.11 to .78 for the second set. It is found that the whole test has ‘average’ level of difficulty and is ‘good’ at discriminating between high and low achieving test takers; to be used for the actual research, a revision of the test is done to eliminate the ‘bad’ items.ABSTRAKKecakapan bahasa Inggris guru dapat diukur dengan merancang instrumen penelitian dalam bentuk tes. Tes yang dirancang harus memenuhi persyaratan tes yang baik. Artikel ini bertujuan membahas analisis soal yang berpusat pada pertanyaan pilihan ganda yang digunakan untuk mengukur kemahiran guru-guru SMA Indonesia yang terlibat dalam pengajaran Bahasa Inggris. Tes set kesatu yang berorientasi silabus diujicobakan pada 20 subjek. Set kedua - berorientasi Bahasa Inggris umum - diujicobakan ke 28 subjek. Analisis tes menunjukkan bahwa indeks kesulitan soal berkisar dari .20 hingga 1 untuk set pertama dan .07 hingga .89 untuk set kedua. Terkait analisis diskriminasi item, studi ini menemukan bahwa nilai D berkisar dari -0,33 ke 1,0 untuk set pertama, dan -0,11 hingga 0,78 untuk set kedua. Ditemukan bahwa keseluruhan tes memiliki tingkat kesulitan 'rata-rata' dan 'baik' dalam membedakan antara peserta tes berprestasi tinggi dan rendah. Untuk digunakan dalam penelitian aktual, revisi tes dilakukan dengan menghilangkan soal 'buruk'. How to Cite: Tamah, S. M., Lie, A. (2019). Analysis of a Research Instrument to Map English Teachers’ Proficiency. IJEE (Indonesian Journal of English Education), 6(1), 48-64. doi:10.15408/ijee.v6i1.11888